Microbiologic and Cytologic Assessment of Bronchoalveolar Lavage Fluid from Dogs with Lower Respiratory Tract Infection: 105 Cases (2001–2011). (30th January 2013) - Johnson, L.R.; Queen, E.V.; Vernau, W.; Sykes, J.E.; Byrne, B.A.
Abstract : Background: Documentation of lower respiratory tract infection has relied on microbiologic and cytologic findings in airway fluid, but there is no gold standard for making a definitive diagnosis. Objective: To report cytologic and microbiologic findings in dogs diagnosed with lower respiratory tract infection through evaluation by bronchoscopy and bronchoalveolar lavage. Animals: A total of 105 dogs with spontaneous respiratory disease. Methods: Retrospective case review of all dogs identified through the electronic medical record database that had bronchoscopy with bronchoalveolar lavage performed between 2001 and 2011. Results of bronchoalveolar lavage cytology and microbiology were evaluated in 510 dogs, and 105 cases with septic, suppurative inflammation or bacterial growth from cultures were examined further. Results: Bacteria were isolated from 89/105 aerobic cultures, 18/104 anaerobic cultures, and 30/99 Mycoplasma spp. cultures. The most common isolate was Mycoplasma spp. followed by Pasteurella sp., Bordetella sp, Enterobacteriaceae, and anaerobes. A single bacterial species was cultured from 44/99 dogs (44%) and multiple bacterial species were isolated from 55/99 dogs (56%). Suppurative inflammation with intracellular bacteria was identified cytologically in 78 of 105 dogs (74%). In 27 dogs that lacked cytologic evidence of sepsis, mixed (n = 18) and neutrophilic (n = 9) inflammation was reported, and Mycoplasma spp. (13/27) or Bordetella spp. (7/27) were most commonly isolated. Most aerobic bacteria were susceptible to routinely used antimicrobial drugs. Conclusions and Clinical Importance: Confirmation of lower respiratory tract infection in dogs is challenging and organisms can be isolated from dogs in which bacteria are not detected on cytologic examination.